PENGUKUHAN MITOS PADA CERPEN BAMBANG KARIYAWAN - nfn Sarmianti (Madah: Jurnal Bahasa dan Sastra, 2016)
Myth and contra myth always exist in human beings life. Hence, both of them also exist in literary work. The existence of myths and contra myths in literary work can always be freedom or concerned. In the two short stories “Numbai” and “Lukah yang Tergantung di Dinding”, the myths are also presented by the authors and are attempted to be freedom by the new myths or contra myths. By applying structural analysis, the intrinsic elements of the myth and contra myth will be discovered. In these two short stories, the myths were presented from the beginning of the story and each of intrinsic elements supports the existence of myths. The myths are strengthened by the accidents that undergone by the main characters, as the agent who destroys myth. The meanings that can be taken from these two short stories are children must obey their parents.